The Purpose Driven Life : What on Earth Am I Here For? - Warren, Rick 1954- (Grand Rapids, Mich. : Zondervan, 2002)
Offers spiritual fulfillment through an understanding of God's plan for a meaningful life
What on earth am I here for? -- Purpose #1: You were planned for God's pleasure -- Purpose #2: You were formed for God's family -- Purpose #3: You were created to become like Christ -- Purpose #4: You were shaped for serving God -- Purpose #5: You were made for a mission
Includes bibliographical references (pages 327-334)
Accelerated Reader
Keywords: Christian life; Christianity; Religious materials